Biocontrol Treatments Confer Protection Against Verticillium dahliae Infection of Potato by Inducing Antimicrobial Metabolites - A. El Hadrami; L. R. Adam; F. Daayf (Molecular Plant-Microbe Interactions, 2011)
Verticillium wilt, caused by Verticillium dahliae Kleb., is a serious potato (Solanum tuberosum L.) disease worldwide, and biocontrol represents a promising eco-friendly strategy to reduce its impact. We used extracts from Canada milk vetch (CMV) and a set of four V. dahliae–antagonistic bacterial strains to coat potato seeds at planting and examined the degree of protection provided against V. dahliae as well as accumulation of soluble phenolics as markers for induced resistance. All tested treatments were effective in reducing disease severity, and CMV showed the highest level of protection. In this treatment, flavonol-glycoside rutin was a highly abundant compound induced in potato tissues, with levels two to three times higher than those detected in noninoculated controls and V. dahliae–inoculated plants. We investigated dose-dependent effects of rutin on V. dahliae growth and sporulation in vitro and in planta. The effect of rutin on mycelial growth was inconsistent between disk assay and amended medium experiments. On the other hand, significant reduction of V. dahliae sporulation in vitro was consistently observed starting at 300 and 100 μM for isolates Vd-9 and Vd-21, respectively. We successfully detected 2-protocatechuoylphloroglucinolcarboxylic acid (2-PCPGCA) using ultra-performance liquid chromatography tandem mass spectrometry, indicating that V. dahliae dioxygenally oxidizes quercetin. Quercetin, as an aglycone, is freed from the sugar moiety by glucosidases and rhamnosidases produced by the fungus and is a substrate for quercetinases. The occurrence of quercetinases in V. dahliae provides a background to formulate a hypothesis about how by-product 2-PCPGCA may be interfering with potato defenses.